ULTRASTRUCTURAL CHANGES IN HEMOMICROCIRCULATION AND PANCREATIC PARENCHYMA IN THE DEVELOPMENT OF EXPERIMENTAL ACUTE PANCREATITIS IN RATS - Zinenko, D.Yu.; Tverdokhlib, I.V. (World of Medicine and Biology, 2017)
The question of the role of microcirculatory changes in the development of adaptive-compensatory or destructive processes, depending on the depth of the pathomorphological alterations of the pancreas, are relevant. There are no complex morphological studies of different models of pancreatitis, taking into account parenchymal changes in the gland, the state of microcirculation in the organ and their interaction at the ultrastructural level. The purpose of the study is to determine early ultrastructural changes in the microcirculatory channel in the pancreas in experimental acute pancreatitis. Ultrastructural changes in the microcirculatory bed and parenchyma of the pancreas in rat models of acute pancreatitis after administration of L-arginine and sodium taurocholate in various doses, were studied. Common early signs of pancreatitis development were revealed by transmission electron microscopy: 1) deformation and destruction of the arteriolar wall; 2) hypoxic damage of the fenestrated endothelium of hemocapillary in pancreatic islets and vessels of the insulo-acinar portal system; 3) erythrocyte shedding and thrombosis of somatic hemocapillaries in pancreatic acini with endothelial fragmentation; 4) dilatation and depletion of the drainage elements of the microcirculatory bed. Micro vessels of the insulin-acinar portal system on the luminal surface have numerous microvilli, which suggests that the degree of influence of hypoxia increases. The wall of these microvessels has signs of intercellular and cytoplasmic edema. Somatic hemocapillaries expand considerably, their internal relief contains a considerable amount of invaginations and microvilli. Endothelial cell cytoplasm contains single micropinocytosis vesicles, swollen mitochondria with fragmented crystals, a small amount of ribosomes and granular endoplasmic network elements. There is a significant expansion of the lumen of venules. The solid wall of the venule has distinct signs of intercellular edema and atrophy of endothelial cells and pericytes. It has been established that the degree of hemocirculation damage depends on the dose of L-arginine or sodium taurocholate, which further determines the level of parenchymal disorders, as well as the scenery and rates of compensatory-adaptive or destructive changes in the pancreas structure. Normalization of the intracellular structure of the exocrine and endocrine cells, cells of the wall of the pancreatic microvessels after administration of L-arginine in a dose of 3 g / kg occurs 24 hours after the onset of simulated acute pancreatitis; after administration of 50 μl of a 1% solution of sodium taurocholate – after 72 hours. The use of L-arginine in a dose of 4 g / kg and 50 μl of a 3% solution of sodium taurocholate leads to a series of irreversible ultrastructural changes of exocrine and endocrine cells with a violation of their secretory cycle, which is partially offset by rearrangements of the microcirculatory channel through the formation of new primitive somatic type hemocapillars. Modeling of acute pancreatitis with the use of L-arginine in doses of 5 g / kg and 50 ml sodium taurocholate concentration of 5% is accompanied by high mortality of animals (80%) within three days of the experiment due to blockage of trans exchange of parenchyma gland deep degradation of mitochondria and ultrastructure protein synthesis in exocrine cells, microvascular thrombosis progressing, strengthening intercellular manifestations of pancreatic toxemia.